Life Course Statuses of Justice-Involved Youth Transitioning to Adulthood: Differences and Change in Offending and Mental Health - Leverso, John (Journal of developmental and life-course criminology, 2023)
Compared to their peers, youth in the juvenile justice system have greater prevalence of mental health problems and a higher likelihood of involvement in delinquency. But little is known about mental health and offending outcomes over time during the transition to adulthood for this population. Using hierarchical linear modeling and data from 1829 individuals recruited to the Northwestern Juvenile Project, we use four time periods, covering approximately 5 years, to look at these outcomes. We operationalize mental health problems as mood disorders and investigate the correlation between offending and mood disorder over time. We then investigate the impact of life course statuses (e.g., marriage, cohabitation, work, and relationships) on mood disorders and offending, both for the overall sample and within sex and age groups. Findings suggest that mood disorders and offending are positively associated across time, and various life course statuses are associated with offending over time, net of mental health problems. Conversely, the same life course statuses had little impact on mood disorders during this period, which were more related to early events such as maltreatment, individual functioning, and mental health histories, with observed differences by sex. These findings illuminate both similarities and divergent patterns that may drive the association between mental health and offending during the transition to adulthood for justice-involved youth.